(untitled) (Experimental biology, 2015)
Growth factor signaling promotes anabolic processes and stimulates cell growth, proliferation, and survival by activation of the phosphoinositide 3-kinase (PI3K)/Akt pathway. Akt phosphorylation of GSK3β inhibits its enzymatic activity and stimulates glycogen synthesis. GSK3β itself is a negative regulator of Akt that acts by controlling mammalian target of rapamycin complex 2 (mTORC2), one of the activating kinases of Akt. Under stress conditions the mTORC2 component rictor is highly phosphorylated by GSK3β on its Ser-1235 site. This phosphorylation event caused inhibition of the mTORC2 kinase activity. In this paper we show that this phosphorylation site is important for cell proliferation and tumor growth.